Impact of Steam Power Plant X Wastewater Disposal on Phytoplankton Community Structure and Coastal Water Quality in South Lampung - Ramadhina, Melati Rizki; Susanto, Gregorius Nugroho; Alfarisi, Salman; Tugiyono, Tugiyono (Jurnal Biologi Tropis, 2024)
Steam power plant is a power plant that uses steam energy as the main turbine engine to produce electricity. Most steam power plant are built in coastal areas because it requires water for its utilization as waste heat or coolant from the surrounding environment. The construction of steam power plant in coastal areas has caused several issues, such as hot water waste, coal waste, mud, sand, and others that can affect the quality of coastal waters and alter the biological composition in the ocean. The purpose of this research is to determine the impact of Steam Power Plant X wastewater disposal on the phytoplankton community structure and coastal water quality in South Lampung. The sampling points were taken at 3 stations in March-April 2024. Water samples were analyzed using 3 parameters: physics, chemistry and biology, with seven optional parameters measured both ex situ and in situ, namely pH, temperature, salinity, brightness, TSS, nitrate and plankton. Based on the results, the disposal of wastewater from Steam Power Plant X has an impact on the phytoplankton community structure, resulting an increase in dominance of phytoplankton species and causing an increase in physical parameters such as temperature and brightness that exceed environmental quality standards.